Nilai Etika dan Relevansi Geguritan Pengajaran Sebagai Media Penyaji Ajaran Agama Hindu - I Kadek Abdhi Yasa (Maha Widya Duta : Jurnal Penerangan Agama, Pariwisata Budaya, dan Ilmu Komunikasi, 2021)
Literary works are created from intuition and expressed in the form of ideas by authors who convey messages to the entire community. In addition, Hindu literary creations contain various moral messages. However, there needs to be an in-depth study to understand the moral message contained in it. Geguritan's Pengajaran is one of the traditional Balinese literary works, the author tends to tell stories well based on the conditions of existence of a literary work. Therefore, this Geguritan Pengajaran is very important to learn because it contains very noble Pengajaran as guidelines in living religious life. Pengajaran Geguritan's is a classic (traditional) literary work that uses pupuh, namely pupuh jerum. Poetry consists of 111 stanzas, each of which consists of 8 lines. Pengajaran Geguritan's presents fictional stories that contain ethical values. The ethical values shown were so much respect byparents I Nengah's for a child that wanted to propose in the end Ni Wayan. However, attitude I Nengah's towards his parents was not praiseworthy because his words were tinged with anger and accompanied by a raised hand. The value of Hindu religious education is very relevant to Geguritan Pengajaran.Keywords: Geguritan Pengajaran, Ethical Value